Редкоземельные элементы в крови млекопитающих Сибири и Дальнего Востока - Барановская Н. В. Наталья Владимировна (2024, 2024)
As a result of work carried out in Siberia and the Far East of Russia, the average contents and fluctuations ranges of 15 rare earth elements (La-Lu) in the blood of three mammals species (Cervus elaphus, Sus scrofa, Sus scrofa domesticus) were determined. The total number of samples was 32.The determination was carried out using ICP-MS in the TPU laboratory, Tomsk. The work was carried out jointly by employees of TPU, TIG FEB RAS and DVGI FEB RAS within the framework of the Russian Science Foundation grants (No. 20-67-47005, 20-64-47021) during 2020–2023. Content ranges and arithmetic averages have been established for all lanthanides. It was revealed that the maximum values occur in the animals blood of the Primorsky Territory. The amount of rare earth elements ranges from 0.001 to 0.6 mg/kg (dm), which does not contradict the data available in the literature.